Postoperative nursing care of a pediatric patient with spastic cerebral palsy (1例痉挛型脑瘫患儿的术后护理体会) - WANG Ting (王婷); LI Jie (李杰); LIU Yang (刘扬); FU Jingna (付景娜); LIU Guyi (刘谷一); TIAN Yixian (田忆贤); HU Yiyuan (胡译元); ZOU Fang (邹芳); ZHAO Yu (赵瑜); WANG Xufeng (王旭凤); ZHAO Haijie (赵海杰); CHENG Lili (程丽丽); et al. (Association of Integrative Nursing, 2023)
This paper summarized the postoperative nursing management of a child with spastic cerebral palsy. The child received selective posterior rhizotomy followed by preoperative examination and preparation. In addition to the interventions on postoperative pain, constipation and infection, a rehabilitation exercise program was carried out to improve the comprehensive recovery of the child after surgery. (本文总结1例痉挛型脑瘫患儿的术后护理体会。患儿入院后完善相关检查和术前准备, 采用选择性脊神经后根切断术治疗, 术后做好疼痛、便秘、感染等护理干预, 根据恢复期制定康复方案, 指导患儿及家属进行康复锻炼, 促使其全面康复。)